Identifying and Evaluating a Model for Enhancing the Assessment of Internal Controls and Accounting Systems - Hajiani, Hadi; Hossein Afshari, Mehran; Rezaei, Mehdi (Business, Marketing, and Finance Open, 2024)
The objective of this study is to identify and evaluate a model to enhance the assessment of internal controls and accounting systems. The study is categorized as an applied-developmental research project. Using purposive sampling, 20 experts in the fields of accounting, auditing, financial management, and organizational management were interviewed. In the quantitative phase, all active participants in the accounting domain, with an unlimited population, were considered, and based on Cochran's formula, the sample size was determined to be 384 individuals. Data analysis in the qualitative phase employed grounded theory using ATLAS.ti software, while structural equation modeling was used for validation via SMART-PLS software. Based on the designed model, several categories were identified. Causal factors include human resource management, personality traits of accountants, ethical values of accountants, managers' attitudes toward accountants, and accountants' specialized knowledge. Contextual conditions encompass financial discipline, laws and regulations, information transparency, receptiveness to criticism, accountability, and the state of accounting. Intervening conditions highlight the weakness of regulatory bodies, financial pressure, environmental conditions, negligence, and socio-cultural conditions. Strategies focus on education, infrastructure development, financial reporting targeting, policy-making, and information technology. Outcomes include improved organizational image, business growth, and economic productivity. To ensure the effectiveness of these systems, continuous monitoring and evaluation processes are essential. The results should be communicated to senior management for implementing corrective measures based on the findings.